Analysis of Willingness To Pay Parking Service Rates at The Sunrise Beach Tourist Object - Anak Agung Bagus Ngurah Nararya Nata; Ni Nyoman Reni Suasih (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
Tourism is an important sector in the Indonesian economy, supported by natural beauty, cultural diversity, and rich historical heritage, making it a favorite destination for domestic and foreign tourists. To optimize the benefits of this sector, the government and tourism destination managers implement a Parking Service Tariff policy for visitors. The purpose of this study is to explain the Influence of Individual Income, Individual Preferences, and Views on Brands on Willingness to Pay Retribution. The population of this study was all visitors to Matahari Terbit Beach, Sanur Denpasar whose exact number is unknown (Infinite). The number of samples used in this study was 190 respondents, taken using a purposive sampling technique. The data collection method used a questionnaire distributed online and offline with a google form. The data analysis technique used was multiple linear regression analysis. The results of the analysis showed that individual income, individual preferences, and views on brands had a positive and significant effect on the willingness to pay retribution. This study is expected to provide relevant and useful input for Matahari Terbit Beach managers regarding efforts to improve performance through research results